2021
DOI: 10.1108/jfra-08-2020-0223
|View full text |Cite
|
Sign up to set email alerts
|

Corporate ethical behavior and the cost of equity capital: evidence from the world’s most ethical companies

Abstract: Purpose This paper aims to examine the effect of the corporate ethical approach on the cost of equity capital. This study is conducted on a large international sample on behalf of the world’s most engaged firms from an ethical point of view in 2015. Design/methodology/approach The multivariate linear regression model is used to meet the purpose of this study and research hypotheses are also examined using a sample of 80 of most ethical firms in the world during the year 2015. Moreover, three variables (i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…Moreover, the influence of the pollutant sector (POL_SECTOR) on French firm decisions has become a widely discussed subject in academia. With respect to the present work, one could note that this control variable turns out to be positively and significantly correlated (at the 5% level) with the cost of equity, which makes it possible to reduce information asymmetry [46]. Finally, we find a significant positive relationship between the book-to-market ratio (BTM) and cost of equity (β = 0.0292, p < 0.05).…”
Section: Discussion Of Resultssupporting
confidence: 52%
“…Moreover, the influence of the pollutant sector (POL_SECTOR) on French firm decisions has become a widely discussed subject in academia. With respect to the present work, one could note that this control variable turns out to be positively and significantly correlated (at the 5% level) with the cost of equity, which makes it possible to reduce information asymmetry [46]. Finally, we find a significant positive relationship between the book-to-market ratio (BTM) and cost of equity (β = 0.0292, p < 0.05).…”
Section: Discussion Of Resultssupporting
confidence: 52%
“…From their meta-analysis, Orlitzky et al (2003) concluded that SRB was positively correlated with CFP. In the same vein, Zouari-Hadiji and Chouaibi (2021) reiterate the prominent notion that socially responsible organizations tend to have a higher valuation and lower risk. In many respects, this stream of research constitutes the major body of knowledge in CSR over the most recent decades.…”
Section: Historical Development Of the Outcome Focus In Mainstream Cs...mentioning
confidence: 84%
“…According to previous studies, corporate ethical standards or values are an effective principle for developing ethical behaviour and generating sound judgments. However, a strong culture and good communication are required to ensure that corporate ethical values are implemented practically in businesses [ 49 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%